Model for Fulfilling the Right to Work for Persons with Disabilities as an Effort to Protect the Law - Asriadi, darmawati; Zainuddin, Asriadi (Jurnal Hukum Volkgeist, 2024)
The issue of fulfilling the rights of people with disabilities is still being discussed today. People with disabilities are often considered as citizens of society who are unable to carry out their duties and responsibilities so that they are sometimes not accepted in the world of work and their rights are often ignored. It is not uncommon for people with disabilities to also have limitations in accessing education due to limited SLB, infrastructure and accessibility for them. This phenomenon is starting to receive attention, especially in Gorontalo Province. The purpose of this study is to find out and analyze the implementation of the fulfillment of work for people with disabilities in Gorontalo Province and find the ideal concept of fulfilling the right to work for people with disabilities. The approach used is a empirical approach with data collection sourced from interviews, questionnaire distribution, literature searches through books, journals, and online media. The results of the study show that the fulfillment of the right to work for people with disabilities has not fully run as expected because it is caused by several factors including discrimination problems, difficulty in obtaining jobs due to the limitations of education and the abilities they have, accessibility and supporting facilities for the fulfillment of the right to education are still limited. The ideal concept of fulfilling the right to work for persons with disabilities is carried out by strengthening the policy framework, strengthening the private sector and the capacity of persons with disabilities and changing the perspective of the public regarding persons with disabilities.